2003
DOI: 10.1080/14636310303141
|View full text |Cite
|
Sign up to set email alerts
|

Rants, Ratings and Representation: ethical issues in researching online social practices

Abstract: This article takes as its field of interest education-related research that is conducted online. It engages directly with issues concerning ethical research conduct when investigating online practices, with reference to studies whose data is drawn solely from cyberspaces, as well as to studies that include an Internet-based investigation component (e.g. studies of what children do when participating in online social spaces outside school, compared with what they do in class in terms of Internet and computer us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Black (2008) described having two separate accounts on Fanfiction.net: one for her fanfiction writer identity and one for her researcher identity. However, Knobel (2003) decided to utilize a single account on eBay, in part to position herself as an experienced user of the space when she approached potential research participants. Regardless of which approach a researcher chooses, establishing a consistent practice of presentation within a networked public remains important.…”
Section: Ethical Dilemmas In Designing and Conducting Literacy Researmentioning
confidence: 99%
See 1 more Smart Citation
“…Black (2008) described having two separate accounts on Fanfiction.net: one for her fanfiction writer identity and one for her researcher identity. However, Knobel (2003) decided to utilize a single account on eBay, in part to position herself as an experienced user of the space when she approached potential research participants. Regardless of which approach a researcher chooses, establishing a consistent practice of presentation within a networked public remains important.…”
Section: Ethical Dilemmas In Designing and Conducting Literacy Researmentioning
confidence: 99%
“…Guided by law and policy, institutional review boards (IRBs) protect both research participants and researchers (Creswell, 2015), but board members are not always knowledgeable about the ethical concerns particular to online research. Most of the discussion of the ethics of online research focuses on: “(1) the distinction between public and private spaces; (2) obtaining informed consent from study participants; and (3) the assurance of participants’ anonymity in research publications” (Knobel, 2003, p. 190). These discussions, and the related decisions of IRBs (known in some countries as human subjects review boards or university ethics committees), while necessary, often do not account for the reality and contextual complexity of contemporary literacy research.…”
mentioning
confidence: 99%
“…The principles are not meant to be prescriptive guidelines, but these are our reflections. For purposes of heuristic convenience, we use the framework similar to the one proposed by Knobel (2003) to describe the research process shown in Figure 1.…”
Section: Qualitative Research In Second Lifementioning
confidence: 99%
“…Research design: A well-designed study (Knobel, 2003) should be grounded in a meaningful problem and should be framed by a well-formed and manageable research question and a workable theory or set of theories; it should involve a careful selection of data collection and data analysis tools and techniques that will produce the kinds of data and outcomes required to address the research questions. A well-planned study should also indicate the time the participants will need to commit to, whether the data collection will occur in two or three stages (e.g.…”
Section: Pre-study Considerationsmentioning
confidence: 99%
See 1 more Smart Citation